Management of toxic epidermal necrolysis with oral involvement with candidiasis in stage III cervical carcinoma patients: Toxic epidermal necrolysis dengan keterlibatan oral disertai kandidiasis pada penderita karsinoma serviks stadium III - Iin Heldayani; Tenny Setiani Dewi (Makassar Dental Journal, 2022)
Toxic epidermal necrolysis (TEN) is the most serious cutaneous adverse drug reaction characterized by extensive detachment of epidermis and erosions of oral mucosal. Early diagnosis and proper therapy are an essential for reduction the morbidity and mortality of this disease. This article is aimed to describe the management of TEN with oral involvement accompanied candi-diasis in patient with carcinoma cervix stage III. A 53-year-old female patient with carcinomacervix stage III and diagnosed of TEN was referred to Oral Medicine Clinic with complaint of painful throughout the oral mucosa, on the lips and during swal-lowing. The patient had a medication history after 25th radiotherapy i.e. cefixime and mefenamic acid. Erythema and erosive le- sion were seen at almost of the bodymainly in back, waist and belly except on palm hand and sole. Erosion also found on the lips with hemorrhagic crusts which bleed easily. Erosive lesion andcandidiasis were seen in the labial mucosa, dorsum and late-ral of tongue, and buccal mucosa. The patient was given NaCl 0.9% for lips compress, chlorhexidinedigluconate 0.12%, hya-ruronic acid mouthwash, vaseline album, whilst therapy for candidiasis was nystatin oral suspension 100,000 IU. The pa-tient was also given education to maintain oral hygiene. It was concluded that oral lesions and candidiasis were healed after 2 weeks of therapy and the patient had significant improvement on the oral mucosal. The appropriate pharmacological and non-pharmacological therapies given were successful on reducing the morbidity and mortality to the patient.